2020
DOI: 10.1001/jamadermatol.2019.4162
|View full text |Cite
|
Sign up to set email alerts
|

Creation of a Registry to Address Knowledge Gaps in Hidradenitis Suppurativa and Pregnancy

Abstract: Vossen ARJV, van Straalen KR, Prens EP, van der Zee HH. Menses and pregnancy affect symptoms in hidradenitis suppurativa: a cross-sectional study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…Currently, no standardized guidelines on the management of HS during pregnancy exist. To address this and other knowledge gaps, the National Hidradenitis Suppurativa Pregnancy Registry is being created, which will collect data on HS disease activity and management, including the use of biologic therapies during pregnancy as well as maternal and fetal outcomes 16 . This registry will supplement the Hidradenitis Suppurativa Prospective Observational Registry and Biospecimen Registry Project (HS PROGRESS) 17 .…”
Section: Pregnancy In Hs Patientsmentioning
confidence: 99%
“…Currently, no standardized guidelines on the management of HS during pregnancy exist. To address this and other knowledge gaps, the National Hidradenitis Suppurativa Pregnancy Registry is being created, which will collect data on HS disease activity and management, including the use of biologic therapies during pregnancy as well as maternal and fetal outcomes 16 . This registry will supplement the Hidradenitis Suppurativa Prospective Observational Registry and Biospecimen Registry Project (HS PROGRESS) 17 .…”
Section: Pregnancy In Hs Patientsmentioning
confidence: 99%
“…Multidisciplinary collaboration is essential in the development of individualized treatment plans for women of childbearing age with HS. Prospective studies ( Adelekun et al, 2020 ) in women with HS are needed to further investigate the impact of delivery method on HS symptoms and improve dermatology and obstetrics/gynecology collaborative counseling of patients with HS regarding the optimal delivery method.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigations are warranted to move this field forward, including mechanistic studies regarding how reproductive hormones impact disease activity, prospective registries to evaluate the efficacy and safety of HS treatments during pregnancy and pregnancy outcomes in patients with HS ( Adelekun et al, 2020 ), implementation of effective targeted strategies to improve sexual function in women with HS, and longitudinal studies to explore the cumulative life course impairment that HS inflicts on patients. These studies would be part of a wider movement within the HS research community to understand the pathogenesis of the disease, expand the therapeutic armamentarium, and hopefully lead to the development of therapeutic and disease biomarkers in HS.…”
Section: Current Knowledge/management Gaps and Future Directionsmentioning
confidence: 99%
“…Hidradenitis suppurativa (HS) is a chronic skin disease with features of autoinflammation and autoimmunity, manifesting as painful nodules and abscesses, as well as malodorous, draining, epithelialized tunnels with a predilection for flexural areas of the skin. As a systemic inflammatory disorder, HS is associated with multiple comorbidities across organ systems, including inflammatory bowel disease, inflammatory arthropathy, as well as metabolic syndrome ( Adelekun et al, 2020 ). In North American and European epidemiologic studies, HS has been found to disproportionately affect women of childbearing age (Adelkun et al, 2021 ; Garg et al, 2021 ; Miller et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%